To what extent is social media marketing localised in an increasingly globalised world? An exploratory study with comparative focus on the creative marketing strategy of Adidas in the United States and the United Kingdom. - Amin, Nikisha (2015)
The primary aim of this study is to identify creative and social media marketing strategies that brands can use to effectively engage with users and consumers, in the context of international advertising. A further objective is to discover cross-cultural marketing strategies in relation to interactivity, and determine if standardisation or localisation is suitable. The study draws on existing literature to outline components of creative brand strategies, what prompts brand engagement, key differences between localisation and standardisation, and the idea of cultural convergence. In order to explore the extent to which social media marketing is localised in an increasingly globalised world, this study adopts a qualitative research approach. The methodology section describes qualitative and quantitative research, various data collection methods, and data analysis. The methods employed for this research are a thematic content analysis of interviews and social media content. The preceding section of the paper analyses results linking to theory. Findings suggest a mixture of standardisation and localisation is preferred amongst participants, and content analysis reveals brands can be successful through the implementation of content appealing to psychological and physical needs of the consumer. The identification of research gaps and suggestions for further research is a clear outcome of the discussion. The paper concludes with a section describing implications of findings on international marketing theory and practice. Limitations suggest time and financial resources contributed to the small scale of the study. Subsequently, recommendations for further research on social media marketing and brand engagement are included.